Prevalence of PIK3CA mutations in Taiwanese patients with breast cancer: a retrospective next-generation sequencing database analysis - Chao, Ta-Chung; Tsai, Yi-Fang; Liu, Chun-Yu; Lien, Pei-Ju; Lin, Yen-Shu; Feng, Chin-Jung; Chen, Yen-Jen; Lai, Jiun-I.; Hsu, Chih-Yi; Lynn, Jiun Jen; Huang, Chi-Cheng; Tseng, Ling-Ming (Frontiers in Oncology, 2023)
Background: Breast cancer is the most common cancer type that affects women. In hormone receptor-positive (HR+), human epidermal growth factor receptor 2−negative (HER2-) advanced breast cancer (ABC), phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha (PIK3CA) is the most frequently mutated gene associated with poor prognosis. This study evaluated the frequency of PIK3CA mutations in the Taiwanese breast cancer population.Methodology: This is a retrospective study; patient data were collected for 2 years from a nextgeneration sequencing database linked to electronic health records (EHRs). The primary endpoint was the regional prevalence of PIK3CA mutation. The secondary endpoints were to decipher the mutation types across breast cancer subtype, menopausal status, and time to treatment failure after everolimus (an mTOR inhibitor) or cyclin-dependent kinase 4/6 (CDK4/6) inhibitor treatment.Results: PIK3CA mutations were identified in 278 of 728 patients (38%). PIK3CA mutations were reported in 43% of patients with HR−/HER2+ subtype and 42% of patients with HR+/HER2-postmenopausal status. A lower prevalence of PIK3CA mutations was observed in triple-negative (27%) and HR+/HER2-premenopausal patients (29%). The most common mutation was at exon 20 (H1047R mutation, 41.6%), followed by exon 9 (E545K mutation, 18.9% and E542K mutation, 10.3%). Among patients treated with CDK4/6 inhibitors, the median time to treatment failure was 12 months (95% CI: 7-21 months) in the PIK3CA mutation cohort and 16 months (95% CI: 11-23 months) in the PIK3CA wild-type cohort, whereas patients receiving an mTOR inhibitor reported a median time to treatment failure of 20.5 months (95% CI: 8-33 months) in the PIK3CA mutation cohort and 6 months (95% CI: 2-9 months) in the PIK3CA wild-type cohort.Conclusion: A high frequency of PIK3CA mutations was detected in Taiwanese patients with breast cancer, which was consistent with previous studies. Early detection of PIK3CA mutations might influence therapeutic decisions, leading to better treatment outcomes.